Pemanfaatan Trichoderma sp. untuk Pengendalian Penyakit Layu Bakteri pada Tanaman Kentang (Solanum tuberosum L.) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
One of the main diseases in potato crops is bacterial wilt disease caused by the bacterium R. solanacearum. Control of this disease can be done by utilizing biological agents Trichoderma sp. which can symbiotic mutualism with plant roots.  The role of the fungus is very important in providing auxin signals and stimulating plant growth. The purpose of this study was to determine the effect of utilizing Trichoderma sp. in suppressing the attack of bacterial wilt disease on potato plants. The research was conducted from August to October 2021 in Insil induk Village, East Passi Subdistrict, Bolaang Mongondow Regency. The study used a Randomized Group Design with 4 treatments and 4 replications. Each treatment consisted of 30 plants, namely; A = Trichoderma sp. (50 gr/plant), 1 week before planting, B = Trichoderma sp. (50 gr/plant), at planting, C = Trichoderma sp. (50 gr/plant), 1 week after planting, D = Control, repeated 4 times. Observations of disease symptoms in the field showed that potato plants attacked by bacterial wilt disease were characterized by the upper leaves curling down or wilting, then the lower leaves were seen to change color from yellowish to brownish, then the stems were brownish, slimy, gave off a distinctive aroma and the tubers when cut looked grayish rotten and gave off mucus. The percentage of R. solanacearum bacterial wilt disease attack on potato plants was highest in treatment D at 56.66%, followed by treatment B at 51.66%, treatment A at 48.33% and treatment C at 46.66%. The results showed that Trichoderma sp. treatment given 1 week before planting, was not able to suppress bacterial wilt disease but had an effect compared to the control treatment (no Trichoderma sp. treatment).